Does strength of tenure rights among the urban poor improve household economies? Contrasting Matero and George in Lusaka city. Issue 1 (2nd January 2018) - Muyeba, Singumbe
ABSTRACT: In a perspective shifting approach, Payne showed that tenure security exists on a continuum from weak to strong tenure rights, rather than as de facto versus de jure categories. This article examines claims that stronger tenure rights improve property values, credit access, employment, household income and participation in income-generating activities among the poor. The article contrasts these outcomes between households with leasehold and occupancy rights in two low-income urban neighbourhoods in Lusaka. The paper draws on household survey data ( n = 623) and in-depth qualitative interviews. Multiple regression analysis is utilized and propensity score matching methods are employed to overcome selection bias. The results show that leasehold rights are associated with significantly higher property values and less participation in income-generating activities. Poorly performing macroeconomic factors – such as high unemployment – may drive household economies so strongly that stronger rights make little impact on employment status, access to credit and household income.